Structural Repetition Detector for multi-scale quantitative mapping of molecular complexes through microscopy - Afonso Mendes; Bruno M. Saraiva; Guillaume Jacquemet; João I. Mamede; Christophe Leterrier; Ricardo Henriques (Nature Communications)
Abstract From molecules to organelles, cells exhibit recurring structural motifs across multiple scales. Understanding these structures provides insights into their functional roles. While super-resolution microscopy can visualise such patterns, manual detection in large datasets is challenging and biased. We present the Structural Repetition Detector (SReD), an unsupervised computational framework that identifies repetitive biological structures by exploiting local texture repetition. SReD formulates structure detection as a similarity-matching problem between local image regions. It detects recurring patterns without prior knowledge or constraints on the imaging modality. We demonstrate SReD’s capabilities on various fluorescence microscopy images. Quantitative analyses of different datasets highlight SReD’s utility: estimating the periodicity of spectrin rings in neurons, detecting Human Immunodeficiency Virus type-1 viral assembly, and evaluating microtubule dynamics modulated by End-binding protein 3. Our open-source plugin for ImageJ or FIJI enables unbiased analysis of repetitive structures across imaging modalities in diverse biological contexts.